ANALYSIS OF VELOCITY ANOMALIES AND RESULTS OF SEISMIC DATA DYNAMIC INTERPRETATION IN THE STUDY OF COMPLEX GAS RESERVOIRS - RUSACHENKO, Nataliia; KUZMENKO, Pavlo; VYZHVA, Serhii (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. One of the priority tasks of geophysics is to detect hydrocarbon accumulations at an early stage of exploration, before drilling the first well, when only seismic data are available. Analysis of elastic wave velocity anomalies together with the results of quantitative interpretation of seismic data is an additional tool for outlining the distribution of reservoir rocks. This is especially relevant for complex deposits in the salt dome zones of the DDB (Dnieper-Donetsk basin). Methods. When the rock is saturated with fluids, its density and elastic waves propagation velocity change, which affects the reflection and transmission of seismic waves. Changes in seismic amplitudes and velocities indicate signs of the presence of various fluids, such as oil, gas or water, thereby helping to identify reservoir fluids. Also, indirect diagnostic tools are AVO analysis and elastic inversion. Results. Six gas fields in the DDZ territory were analyzed, which have identical seismic field characteristics within the gas deposit. The integral influence of a porous saturated layer on the amplitudes, frequencies and propagation velocities of elastic waves was described. Conclusions. As a result of a comprehensive analysis of seismic data, a methodology was described that allows assessing the key characteristics of the reservoir and, at the same time, identifying gas traps or areas of hydrocarbon accumulation inherent in the DDB region.